How the product-harm crisis influences consumer boycotts: the role of social distance - Yalin Li; Min Zhao (Humanities & Social Sciences Communications)
Abstract Product-harm crises can be categorized into two types on the basis of the number of enterprises involved: single-enterprise and group product-harm crises. Although the incidence of group product-harm crises is increasing, prior research has focused predominantly on single-enterprise product-harm crises, with limited attention paid to group product-harm crises, particularly their impact. This study aims to examine how a product-harm crises influence consumer boycott behaviour by investigating the mediating role of blame attribution and perceived betrayal, as well as the moderating role of social distance. Through a scenario-based experimental survey, three studies were conducted, collecting a total of 726 samples to test the hypotheses. The results indicate that consumers exhibit stronger boycott intentions in response to group product-harm crises than in response to single-enterprise product-harm crises. Crucially, this effect is mediated by blame attribution and perceived betrayal. Additionally, social distance moderates the relationships between product-harm crises and consumer boycotts, perceived betrayal, and blame attribution.